Pemuridan kepada Remaja dan Pemuda di Gereja Kristen Pasundan Sindangjaya - Sihombing, Aeron Frior; Sadikin, Vivian; Tampubolon, Yohanes Hasiholan; Binti, Ayu Apriolita; Rohi, Ferdy (Society : Jurnal Pengabdian Masyarakat, 2023)
GKP Sindangjaya is a congregation that has established a partnership with STT SAPPI for community empowerment. The PkM approach begins with a survey to analyze the issues faced by youth in GKP Sindangjaya. Three main issues were identified: the inconsistency in the attendance of youth, their limited active involvement in the church, and social insecurity among them. The proposed solution is discipleship, involving the formation of a community with the goal of producing committed disciples of Christ. This process involves building deep relationships and effective communication. The PkM activities are designed in accordance with the research areas in the road map of LPPM STT SAPPI, including education, agribusiness, religion, and applied technology. The stages include preliminary surveys, the implementation of various discipleship and social interaction activities, monitoring, evaluation, report preparation, and publication in the form of a journal. The hope for this PkM is that the youth being mentored will exhibit more consistent attendance, active involvement in the church, and improved self-confidence in expressing their opinions. Through this approach, PkM is expected to have a positive impact on the personal and social development of youth in GKP Sindangjaya.